PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2012-2013 - Syafrinaldi, Kiki; -, Zirman; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to test the effect of the board of directors, independent directors, the intensity of the board and the influence of corporate social responsibility to corporate value. The population in this study was all banks in Indonesia Stock Exchange as many as 33 companies. This study used purposive sampling method, then there are 31 conventional banks that listed in Indonesia Stock Exchange on 2012-2013 that meets the criteria of the sample. Analysis of data using multiple regression models. The study states that the Board of Directors does not have a significant effect on firm value. Independent Commissioner has a significant effect on the corporate value. The intensity of the Board have a significant effect on firm value. and Corporate Social Responsibility (CSR) has a significant effect on firm value. This means the Commissioner of the Independent, and the intensity of the Board of Corporate Social Responsibility (CSR) which is a factor that needs to be used as a material consideration in the management of the corporate value.Keywords: Board of Directors, Independent Commissioner, Intensity Board and Corporate Social Responsibility (CSR), Corporate Values